2015
DOI: 10.3349/ymj.2015.56.6.1590
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Foxo3 in Leydig Cells

Abstract: PurposeFoxo3 in female reproduction has been reported to regulate proliferation of granulose cells that form follicles. There are no reports so far that discuss on the role of Foxo3 in males. This study was designed to outline the role of Foxo3 in the testes.Materials and MethodsTestes from mice at birth to postpartum week (PPW) 5 were isolated and examined for the expression of Foxo3 using immunostaining. To elucidate role of Foxo3 in Leydig cells, R2C cells were treated with luteinizing hormone (LH) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…1E, left; control, middle; AKITA, and right; STZ-injected). Immunofluorescence showed uneven expression of AMH in antral follicles in the ovaries of AKITA mice, while it was uniformly expressed in granulosa cells of growing follicles (primary, secondary, and multilayered secondary follicles) 16. Furthermore, the expression of ER, a granulosa cell marker, was barely detectable in the granulosa cells of antral follicles from AKITA and STZ-injected mice, while high expression levels of Ki-67 were detected in proliferating granulosa cells in all three groups (Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…1E, left; control, middle; AKITA, and right; STZ-injected). Immunofluorescence showed uneven expression of AMH in antral follicles in the ovaries of AKITA mice, while it was uniformly expressed in granulosa cells of growing follicles (primary, secondary, and multilayered secondary follicles) 16. Furthermore, the expression of ER, a granulosa cell marker, was barely detectable in the granulosa cells of antral follicles from AKITA and STZ-injected mice, while high expression levels of Ki-67 were detected in proliferating granulosa cells in all three groups (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…1). 16 Three weeks after the blood glucose check, the body weights of control, AKITA, and STZ-injected mice were measured. A total of 150 mice [wild-type C57BL/6J (n=50), AKITA (n=50), and STZ-injected mice (n=50)] were used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Overexpression of FOXO3 in mouse nerve cells significantly promotes their apoptosis [33]. Likewise, overexpressed FOXO3 regulates apoptosis in testicular mesenchymal cells through BCL2L11 activity [34]. Studies have shown that, in follicle granulosa cells, upregulation of FOXO3 can accelerate follicular atresia in pigs, indicating that the FOXO3 protein has a proapoptotic effect on mammalian granulosa cells [35].…”
Section: Resultsmentioning
confidence: 99%
“…Several FOX transcription factors are believed to regulate spermatogenesis in mice: FOXO1, which is expressed in gonocytes and undifferentiated spermatogonial cells, plays a crucial role in the gonocyte‐to‐SSC transition, self‐renewal, and differentiation of SSCs (Goertz et al, ). FOXO3 affects testosterone synthesis within testes by inhibiting the formation of Steroidogenic acute regulatory protein (Choi et al, ). FOXJ2 was recently proposed to control meiosis during spermatogenesis, as loss of FOXJ2 in the male germ line leads to meiotic arrest and complete infertility (Miao et al, ).…”
Section: Introductionmentioning
confidence: 99%